The Influence of Social Media Marketing, Service Quality, and Price Perception on Customer Loyalty - Yulia, Novanda Dara (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
This study investigates the influence of social media marketing, service quality, and price perception on customer loyalty at Nails By Faa Beauty Studio in Malang City. The research explores both direct and indirect relationships between the independent and dependent variables. Employing an explanatory research design, the study utilizes hypothesis testing to examine causal links among variables. A total of 95 respondents—customers who had received treatments more than once and had interacted with Nails_ByFaa’s social media—were selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability testing, classical assumption testing, and multiple linear regression. The findings reveal that social media marketing and service quality significantly and directly affect customer loyalty, whereas price perception does not have a significant impact. These results highlight that, in the service industry, customer loyalty is more strongly driven by experiential and emotional engagement, particularly through social media, rather than by price considerations.